2013
DOI: 10.1177/0022034513482141
|View full text |Cite
|
Sign up to set email alerts
|

Organo-Selenium-containing Dental Sealant Inhibits Bacterial Biofilm

Abstract: Oral bacteria, including Streptococcus mutans and Streptococcus salivarius, contribute to tooth decay and plaque formation; therefore, it is essential to develop strategies to prevent dental caries and plaque formation. We recently showed that organo-selenium compounds covalently attached to different biomaterials inhibited bacterial biofilms. Our current study investigates the efficacy of an organo-selenium dental sealant (SeLECT-Defense TM sealant) in inhibiting S. mutans and S. salivarius biofilm formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 25 publications
3
52
0
Order By: Relevance
“…It contains selenium which in polymer form can produce superoxide radicals [22], causing oxidative stress that damages the bacterial cell wall and DNA [23,24]. In an in vitro investigation, Tran et al, [25] demonstrated the ability of DS sealant to inhibit bacterial attachment and biofilm formation by two of the main culprits in plaque development, namely Streptococcus mutans and Streptococcus salivarius. These bacteria cannot survive under selenium-containing sealant as opposed to regular dental sealants [25].…”
Section: Denteshieldmentioning
confidence: 99%
See 1 more Smart Citation
“…It contains selenium which in polymer form can produce superoxide radicals [22], causing oxidative stress that damages the bacterial cell wall and DNA [23,24]. In an in vitro investigation, Tran et al, [25] demonstrated the ability of DS sealant to inhibit bacterial attachment and biofilm formation by two of the main culprits in plaque development, namely Streptococcus mutans and Streptococcus salivarius. These bacteria cannot survive under selenium-containing sealant as opposed to regular dental sealants [25].…”
Section: Denteshieldmentioning
confidence: 99%
“…In an in vitro investigation, Tran et al, [25] demonstrated the ability of DS sealant to inhibit bacterial attachment and biofilm formation by two of the main culprits in plaque development, namely Streptococcus mutans and Streptococcus salivarius. These bacteria cannot survive under selenium-containing sealant as opposed to regular dental sealants [25]. Furthermore, selenium-containing sealants such as DS, when polymerized, do not leach selenium and are thus believed to sustain their antibacterial effects over time.…”
Section: Denteshieldmentioning
confidence: 99%
“…19 In 2010, Select Defense (ClassOne Orthodontics, Carlsbad, Calif) was introduced as an enamel sealant that contained selenium, an antimicrobial. Tran et al 20 reported that organo-selenium compounds covalently attached to different biomaterials, thus inhibiting bacterial biofilms. The key to protection, however, is the ability of the sealant to remain on the exposed enamel for the duration of treatment without the need for periodic reapplications.…”
Section: S58mentioning
confidence: 99%
“…Thus, they suggest that the application of Se-MAP-coated gauze to the debrided tissues of burn wounds may prevent the development of biofilms and facilitate wound healing. This approach might also be used for dental applications [78] and to combat infections in hospitals caused by catheters and other medical implants.…”
Section: Selenium-carrier Conjugatesmentioning
confidence: 99%